2016
DOI: 10.3762/bjoc.12.49
|View full text |Cite
|
Sign up to set email alerts
|

Copper-mediated arylation with arylboronic acids: Facile and modular synthesis of triarylmethanes

Abstract: SummaryA facile and modular synthesis of triarylmethanes was achieved in good yield via a two-step sequence in which the final step is the copper(II)-catalyzed arylation of diarylmethanols with arylboronic acids. By using this protocol a variety of symmetrical and unsymmetrical triarylmethanes were synthesized. As an application of the newly developed methodology, we demonstrate a high-yielding synthesis of the triarylmethane intermediate towards an anti-breast-cancer drug candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…12 In 2016, Roa and co-worker showed that Cu(OTf) 2 can catalyze the Suzuki reaction of diarylmethanol to generate triarylmethanes in good yields (Scheme 1b). 13 Shi's group has also successfully performed nickel catalyzed cross-coupling reactions of benzylic alcohols using a reactive Grignard reagent as a nucleophilic partner to the alcohol (Scheme 1c). 14 Nickel catalyzed Suzuki cross-coupling reactions of naphthyl and quinolyl alcohols have never been reported.…”
mentioning
confidence: 99%
“…12 In 2016, Roa and co-worker showed that Cu(OTf) 2 can catalyze the Suzuki reaction of diarylmethanol to generate triarylmethanes in good yields (Scheme 1b). 13 Shi's group has also successfully performed nickel catalyzed cross-coupling reactions of benzylic alcohols using a reactive Grignard reagent as a nucleophilic partner to the alcohol (Scheme 1c). 14 Nickel catalyzed Suzuki cross-coupling reactions of naphthyl and quinolyl alcohols have never been reported.…”
mentioning
confidence: 99%
“…One example of the intermolecular Suzuki-Miyaura-type cross-coupling reaction to synthesize a tetracyclic lactam of a neuvamine framework was performed to yield the product 46c in 89% yield. Rao and Rao also applied the Cu(OTf) 2 -catalyzed Suzuki-Miyaura-type cross-coupling reaction to bisbenzylic alcohols (Scheme 8B), 18 and in this way 17 examples of triarylmethanes were obtained in 64-92% yield. A reaction mechanism proceeding through ArCu II (OTf) 48, which was initiated from transmetalation of Cu(OTf) 2 and ArB(OH) 2 , and simultaneous C-O bond cleavage and subsequent C-C bond formation was proposed (Scheme 9).…”
Section: Scheme 8 Transition-metal-catalyzed Di-and Triarylmethane Symentioning
confidence: 99%
“…Low cost, easy availability, and operational accessibility put copper salts as versatile metal catalysts for various C–C bond forming reactions. Therefore without jeopardizing the operational feasibility, copper (II)‐triflates have been utilized by the groups of Rao[40a] and Maiti[40b] for the three‐component coupling synthesis of symmetrical and unsymmetrical triarylmethanes in good yield (Scheme a‐b). The high regio‐ and chemoselectivity, wide substrate scope, excellent functional group tolerance and simplicity of the operation are the definite advantages of these two methods.…”
Section: Synthesis Of Triarylmethanes (Trams)mentioning
confidence: 99%
“…Although Lewis or Brønsted acid‐mediated Friedel–Crafts arylation or traditional metal catalyzed methods have become the prevailing methods to access symmetrical or unsymmetrical TRAMs, the requirement of electron rich arenes, harsh reaction conditions, exotic catalysts, and need for pre‐functionalization of the substrates are the genuine constraints of those methodologies. Very recently, rhodium catalyzed 1,4‐addition of arylboronic acids to ortho ‐quinone methides for the synthesis of TRAMs was disclosed . Although this method has a broad substrate scope and excellent functional group tolerance, the requirement of 100 % atom economy urged the scientific community to explore newer methods.…”
Section: Synthesis Of Triarylmethanes (Trams)mentioning
confidence: 99%